Kadar Beta Karoten dan Daya Terima Cookies Garut dengan Substitusi Tepung Labu Kuning - Noviati, Titik Dwi, Eni Purwani, S.Si.,M.Si, Pramudya Kurnia, S.TP, M.Agr (2016)
Introduction: Public dependence on wheat flour is very high. It is necessary for the development of local food products as a substitute for wheat flour, one of which is the tubers of Garut. Vitamin A deficiency (VAD) is one of the main nutritional problem in Indonesia. One local food that has the potential to be processed into food products and contains a high vitamin A is pumpkin. Therefore, it is necessary to do a research about levels of beta carotene and receptivity of cookies from Garut's flour with pumpkin flour substitution. Research aims: To determine the level of beta carotene and receptivity of cookies Garut with the substitution of pumpkin flour. Research method: This research method was experimental with a completely randomized design with three treatments and one control twice. The pumpkin flour substitution was 0%, 15%, 20% and 25%. The beta carotene and receptivity levels were obtained with spectrophotometer method and a test of 30 panelists. The statistical test of beta carotene and receptivity were analyzed using annova and kruskall wallis continued with Duncan Multiple Range Test. Results: The anova showed the ρ value of beta carotene of cookies at 0.000. The kruskall wallis described the ρ value of receptivity of cookies to colors at 0.000, 0.005 for aroma, 0.015 for texture and 0.000 for all favorite. Conclusions: The highest beta carotene was at 25% substitution. The most preferred cookies Garut of panelists was with the substitution of pumpkin flour at 20%. There pumpkin flour substitution effected on levels of beta carotene and receptivity of cookies Garut. Suggestion: It is necessary to use pumpkin flour substitution 25% for Vitamin A deficiency (VAD). It is necessary to use corn sugar on making garut's cookies that cater to people with Diabetes Mellitus. Special measures need to be done during the manufacturing process to get the receptivity of cookies from Garut's flour are preferred by the panelis.